Dye exclusion technique to assess the viability of pre-implantation bovine embryo based on a murine model - SINGH, GURVINDERJIT; PANGAONKAR, G R; MATHAROO, JOGA SINGH; SINGH, PRAHLAD; SINGH, MEHAR (The Indian Journal of Animal Reproduction, 2023)
Dye exclusion assay was evaluated for assessing viability of pre-implantation murine and bovine embryos along with morphological examination of sucrose-induc<!d shrinkage and in vitro culture. Different concentrations of the dyes were also investigated to determine the optima. A total of 460 murine and 76 bovine embryos, on morphological evaluation revealed 71. 52 and 72.36 per cent viability, respectively. Dye exclusion assay of murine embryos using Trypan Blue (0.05%), Eosin-Y (0.12 tn¥), Rose Bengal Red (0.5 mM) and Eosin-B (0.12 mM) followed by developmental competence indicated 82.35, 81.25, 78.57 and 50.0 per cent viability, respectively. The corresponding values in case of bovine embyros were 80.0, 87.0, 75.0 and 61.5 percent. The differences in viability estimates due to dyes were statistically significant (P<0.05). Sucrose induced shrinkage ofmurine and bovine embryos indicated 71.06 and 65.45 per cent viability respectively. Corresponding values by in vitro culture were 73.62 and 70.9 per cent. The differences between morphological assay and other methods were significant (P<0.05) but the differences between dye exclusion assay and developmental competence of embryos in culture medium were statistically non significant.